S9.1d Chronic pulmonary aspergillosis in post-TB and retreatment TB patients in Lagos, Nigeria. (20th September 2022) - Davies, Adeyinka; Adekoya, Abiola; Oladele, Rita
Abstract: S9.1 Chronic Pulmonary Aspergillosis - where do we stand?, September 23, 2022, 4:45 PM - 6:15 PM: Objectives: Chronic pulmonary aspergillosis (CPA) is a known complication of post-TB treatment. It is a progressive disease characterized by progressive cavitation, fibrosis, and pleural thickening among others. Globally, an estimated 3 million people are affected. This study determined the burden of CPA amongst the post-TB and retreatment TB patients in two facilities in Lagos, Nigeria. Methods: This was a prospective longitudinal study that was carried out at two TB clinics (LUTH and NIMR) in Lagos, Nigeria between February 2021 and March 2022. The study cohorts were patients that had been previously managed (2-4 years earlier) for TB, they were clinically classified as retreatment TB and post-TB patients. Patients were seen in clinics every 3 months and the following data were collected: Quality of life (WHO and SGRO questionnaires used), 5 mls of blood for Aspergillus IgG level (using Bordier; cut-off of 0.8 AU/ML), sputum for culture (those with productive cough), and chest X-ray. Infectious disease society of America (IDSA) case definition was used to determine cases of CPA. Results: A total of 112 post-TB treatment patients were recruited, 60 (53.1%) were retreatment TB and 52 (46.0%) post-TB patients. The mean age was 41.14 years; with the majority between the ages of 21-30 years. The male/female ratio was 0.9/1. 98 (87.5%) were HIV negative, and only 40 patients had GeneXpert testing done. In all 32/40 were GeneXpert negative; of which 24/32 and 8/32 belonged to the retreatment, and post-TB groups respectively. Cough was the predominant symptom with 39 (34.8%) having productive cough. Hemoptysis occurred in 11 (9.8%), 10 in the retreatment group with 2 having frank hemoptysis. Chest imaging revealed that 27/112 of the studied cohort presented with multiple cavities, 4/112 had single cavities, 26/112 had cavities with surrounding opacities and 23/112 had upper lobe consolidation. A total of 17/112 of them had bilateral lung infiltrates and 13/112 had pleural thickening. Sputum culture yielded growth of Aspergillus spp, with A. flavus ( n- 11; 36.7%) being the predominant species followed by A. fumigatus ( n -10; 33.3%), and A. niger ( n -9; 30%). In all 38/112 (33.93%) patients had Aspergillus IgG titer above the cut-off level, while 6 symptomatic patients had borderline Aspergillus IgG levels. A total of 11/112 (9.82%) of the study cohorts with positive Aspergillus IgG levels were also culture positive; 8/68 of the Aspergillus IgG negative patients were culture positive and had abnormal chest imaging reported. A total of 38 (33.93%) were confirmed cases of CPA using IDSA criteria. Of the GeneXpert positive; 7/40 were retreatment TB; 16/32 of GeneXpert negative and 8/40 of GeneXpert positive met the criteria for CPA. Conclusion: Our findings demonstrate that CPA is easily misdiagnosed as treatment failure TB or TB relapse. There is a need for further follow-up of post-TB patients for early identification of post-TB lung disease. It is also imperative to educate our clinicians to screen patients who have persistent symptoms and are GeneXpert negative for other post-TB lung diseases.